Comparison of Sexual Dysfunction in Women Using Depo-Medroxyprogesterone Acetate (DMPA) and Cyclofem - G Ozgoli; Z Sheikhan; M Dolatian; M Simbar; M Bakhtyari; M Nasiri (JRI, 2015)
Background: Sexual affairs are one of the physiological needs affecting human health. Sexual functioning disorders can reduce individual’s capabilities and creativities. Sexual relations are in the center of women’s quality of life. The most important family planning is to prevent unintended pregnancies. Injectable contraceptives protect women exposed to many complications and mortality due to unintended pregnancies, with tolerable effects on other aspects of women’s life. An important aspect of women’s life is sexual health. This study aimed to compare sexual function of women using DMPA with women using Cyclofem presented to health centers affiliated to Shahid Beheshti University of Medical Sciences in Tehran, Iran in 2013. Methods: This descriptive-comparative study was conducted on 240 women in health centers in Tehran, Iran. They were selected by multistage sampling. The data was collected using a questionnaire completed by interviewing. The questionnaire had 2 parts, demographic characteristic section and Female Sexual Function Index (FSFI). Data was analyzed by descriptive statistics, independent T-test, U-test, Chi-square, Fisher exact test. The p-value less than 0.05 were applied for all statistical tests as significance level. Results: The difference in sexual function between Cyclofem and DMPA groups was insignificant, but in terms of sexual desire  in DMPA users better than and sexual pain them less than in Cyclofem users, the difference between the groups was significant (p<0.05). Conclusion: In introducing hormonal contraceptive methods, health workers should emphasize their adverse effects on sexual function. Women who use Cyclofem and DMPA should be aware that they may experience some changes in libido and sexual pain.